Molecular Epidemiology and Clone Transmission of Carbapenem-Resistant Acinetobacter baumannii in ICU Rooms - Zhang, Xiufeng; Li, Fangping; Awan, Furqan; Jiang, Hongye; Zeng, Zhenling; Lv, Weibiao (Frontiers in Cellular and Infection Microbiology, 2021)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is a major cause of nosocomial infections and hospital outbreaks worldwide, remaining a critical clinical concern. Here we characterized and investigated the phylogenetic relationships of 105 CRAB isolates from intensive care unit from one hospital in China collected over six years. All strains carried blaOXA-23, blaOXA-66 genes for carbapenem resistance, also had high resistance gene, virulence factor and insertion sequences burdens. Whole-genome sequencing revealed all strains belonged to ST2, the global clone CC2. The phylogenetic analysis based on the core genome showed all isolates were dominated by a single lineage of three clusters and eight different clones. Two clones were popular during the collection time. Using chi-square test to identify the epidemiologically meaningful groupings, we found the significant difference in community structure only existed in strains from separation time. The haplotype and median-joining network analysis revealed genetic differences appeared among clusters and changes occurred overtime in the dominating cluster. Our results highlighted substantial multidrug-resistant CRAB burden in hospital ICU environment, demonstrated potential clone outbreak in hospital.